Idiopathic Hypertrophic Pyloric Stenosis with Complete Ladd's Band: A Rare Association - Abo Elyazeed, Ahmed M.; Shalaby, Mohamed M.; Awad, Mohamed M.; Effat, AbdelMotaleb M.; Abdella, Ahmed E.; Shehata, Sherif Mohamed (European Journal of Pediatric Surgery Reports, 2019)
A male infant aged 45 days presented with projectile nonbilious vomiting for 2 weeks. Ultrasound showed picture of idiopathic hypertrophic pyloric stenosis. Laparoscopic pyloromyotomy was done, but postoperative vomiting that was mainly nonbilious continued without improvement. After 4 days of persistent vomiting, laparoscopic exploration was done and complete pyloromyotomy was confirmed and malrotation with complete Ladd's band was found, then case converted to open laparotomy and Ladd's procedure was done. Postoperatively, vomiting stopped completely and baby began gradual feeding till reaching full feed. Despite that the presentation of concurrent Idiopathic Hypertrophic Pyloric Stenosis with malrotation is extremely rare; a formal laparoscopic abdominal exploration should be done as the first step before proceeding to pyloromyotomy.
Keywords: laparoscopic pyloromyotomy; malrotation; Ladd's band; Ladd's procedure; laparoscopic exploration; postoperatively; vomiting